Effect of Innovative Glassy House and Secondary Reflectors Combination with Nanocoating on Fast and Slow Increase of Receiver Temperature in Parabolic Solar Collector - Mohammed Ajmi Abd; Alaa Y. Ali (Eximia, 2025)
The purpose of this work is to enhance the ability of the receiver for increasing in temperature absorbing, firstly achieving a rapid rise the temperature in a relatively short time through geometric variables, and secondly, achieving higher temperatures and maintaining them over time for long periods using nano-coatings.The present study related to the development of parabolic dish solar concentrator as a design by using the concept of a glass house with an attempt to invent and manufacture small-sized secondary reflectors to be placed inside the greenhouse which is placed on the side of the receiver at an angle of 45° to reflect the rays that may pass directly without passing through the receiver. The three primary modifications include, copper receiver, a glassy spherical cover, and secondary reflectors. A copper tube is made up of coil in spiral shape and it is fixed in the focus of dish to obtain maximum solar energy. The higher absorber temperature was 58°C with out any modification.The absorber temperature increased with first modification to( 87°C,50%), by using second modification (a glassy spherical ) it was found that the glass cover improved the rapid and greater temperature rise which increased to (132°C, 137%), Also by using of a glassy spherical cover with secondary reflectors (third modification), the increasing absorber temperature are raised to (162°C ,179%). The temperature of the receiver will be less lost with an increase in wind speed in the second and third modifications.Thirdly, a nanocoating was used for each of (CuO, TiO2) to determine the extent to which it is possible to achieve an increase in the absorbed temperature for a relatively long time without any modification once which increased to (71°C,22.4% for CuO nanocoating) and decreased to (50C, -60% for TiO2 nanocoating). Using the third modification with nanocoating and for a relatively long period time, this research found that the temperature increased (175°C,201 % for CuO nanocoating), and ( 115 C, 98% for TiO2 nanocoating).This means that the nanocoating of (TiO2) without an air-tight cover leads to a decrease in the absorption efficiency compared to the absorbing surface alone, but it increases with the use of the third modification, while the coating with (CuO) increases the absorbed temperature in both cases and is more efficient than titanium oxide, the higher temperature difference of the nanocoating is due to higher thermal conductivity of CuO nanoparticles.These results can enhance the improvement of designs used for the same purpose in the future.